Standards of academic accreditation in universities/University of Baghdad as a model (Journal of the College of Basic Education, 2022)
Developing the reality of society, taking care of building its ways of thinking, by adopting modern scientific methods to qualify and develop its members. Information that qualifies them to meet the challenges of education and rehabilitation that the world is witnessing today. It has become imperative for educational institutions to reform their educational systems. Verify the achievement of comprehensive university standards. Accreditation. Determining the objectives of the research, the above classification criteria were identified, the periodic table of universities in the international ranking of universities.